2008
DOI: 10.1016/j.febslet.2008.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of Gln294 of the reverse transcriptase of human immunodeficiency virus type‐2 and its effects on the ribonuclease H activity

Abstract: Despite the high homology between human immunodeficiency virus type-1 (HIV-1) and human immunodeficiency virus type-2 (HIV-2) reverse transcriptases (RTs), the ribonuclease H (RNase H) level of HIV-2 RT is lower than that of HIV-1 RT, while the DNA polymerase of both RTs is similar. We conducted mutagenesis of HIV-2 RT Gln294 (shown to control the RNase H activity level when modified to a Pro in the smaller p54 subunit and not in the larger p68 subunit) to various residues, and assayed the activities of all mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…When the Gln was replaced by a Pro, either in both HIV-2 RT subunits or only in the smaller subunit, the resulting HIV-2 RT showed an about tenfold increase in its RNase H activity in comparison to the wildtype RT [39,40]. Interestingly, changing Gln294 of HIV-2 RT p55 to residues that represent all amino acid groups (except for a Gln) has also resulted in an increase in the RNase H activity [120]. The interactions between the polymerase and the RNase H domains may be particularly important in the case of HIV-1 and HIV-2 RTs, since the expression of the smaller subunit of the RTs (p51 and p55, respectively), which lacks the entire RNase H domain, results in an enzyme with a very low DNA polymerase activity [16,121].…”
Section: The Rnase H Activity Of Rtmentioning
confidence: 99%
“…When the Gln was replaced by a Pro, either in both HIV-2 RT subunits or only in the smaller subunit, the resulting HIV-2 RT showed an about tenfold increase in its RNase H activity in comparison to the wildtype RT [39,40]. Interestingly, changing Gln294 of HIV-2 RT p55 to residues that represent all amino acid groups (except for a Gln) has also resulted in an increase in the RNase H activity [120]. The interactions between the polymerase and the RNase H domains may be particularly important in the case of HIV-1 and HIV-2 RTs, since the expression of the smaller subunit of the RTs (p51 and p55, respectively), which lacks the entire RNase H domain, results in an enzyme with a very low DNA polymerase activity [16,121].…”
Section: The Rnase H Activity Of Rtmentioning
confidence: 99%
“…In the HIV-1 RT, the same protein surface area has a positive charge and presents a Pro in the 294 residue [33]. Interestingly, when the HIV-1 RT 294 Pro residue is mutated in Gln the HIV-1 RNase H activity is reduced and, conversely, when the HIV-2 RT 294 Gln residue is mutated in Pro the HIV-2 RNase H activity is 10 fold increased [32,33]. The observation that mutations in the small subunit strongly influences RT activities clearly confirms the fine interplay between the two subunits and the importance of the overall enzyme architecture which has been also demonstrated by other several studies, including also the ones on HIV-1 RT drug resistance [6,34].…”
Section: Hiv-2 Rnase Hmentioning
confidence: 87%
“…It is also worth to highlight that, beside the 10-fold difference between the RNase H activity of HIV-1 and HIV-2, both viruses effectively replicate raising the question whether it is the HIV-2 that has a low level of RNase H function or it is the HIV-1 which has an high level of enzyme activity [27]. However, the fact that it has been reported that the great majority (if not all) of the HIV-2 isolates present the Gln in position 294 [32] seems to substantiate the latter hypothesis.…”
Section: Hiv-2 Rnase Hmentioning
confidence: 93%
See 1 more Smart Citation
“…(iv) RNase H. This assay was performed as described earlier by us (17)(18)(19)25). Each assay contained ϳ0.1 pmol of the 5=-32 P-end-labeled RNA transcript (E11), which was annealed to 0.4 pmol of a 20mer synthetic oligonucleotide DNA (E10 in Table 1).…”
Section: Methodsmentioning
confidence: 99%